Development of instruments for DIVAYANA evaluation model - Divayana, Dewa Gede Hendra; Suyasa, P Wayan Arta; Widiartini, Ni Ketut (Research and Social Study Institute, 2021)
The purpose of this research showed a valid DIVAYANA evaluation model instruments were used to evaluate the implementation of e-learning. This research approach was the development of evaluation instruments. The evaluation instruments developed were in the form of interview guides and questionnaires. The interview guidelines that resulted were related to several DIVAYANA evaluation components, included: the Description component, Input component, Verification component, and Yack component. Questionnaires were generated on several DIVAYANA evaluation components, included: the Verification component, Action component, and Yack component. The subjects involved in the content validity test of the interview guidelines were two experts, including an informatics education expert and an educational evaluation expert. The content validity tests of questionnaires were conducted by six experts, including three education evaluation experts and three informatics education experts. The content validity calculation process of the interview guidelines used the Gregory formula, while the content validity of the questionnaires used Lawshe’s CVR formula. The content validity average of interview guidelines on the Description, Input, Verification, and Yack components was 0.882 so it was included in the very good category. The content validity average of questionnaires on the Verification, Action, and Yack components was 0.774 so it was in a good category. The implication of this research is the realization of valid measuring instruments that can be used in evaluating the implementation of e-learning.